Translation and cross-cultural adaptation of the Clinical Competence Questionnaire for use in Brazil - Danielle Ritter Kwiatkoski; Maria de Fátima Mantovani; Evani Marques Pereira; Carina Bortolato-Major; Ângela Taís Mattei; Aida Maris Peres (Revista Latino-Americana de Enfermagem)
ABSTRACT Objective: translating and transculturally adapting the Clinical Competence Questionnaire to Brazilian senior undergraduate Nursing students, as well as measuring psychometric properties of the questionnaire. Method: a methodological study carried out in six steps: translation of the Clinical Competence Questionnaire instrument, consensus of the translations, back-translation, analysis by an expert committee, pre-testing and then presentation of the cross-cultural adaptation process to the developers. Psychometric properties were measured using Cronbach's alpha, intraclass correlation coefficient and content validity index. Results: the instrument was translated, transculturally adapted and its final version consisted of 48 items. Cronbach's alpha coefficient was 0.90, and the agreement index of the items was 99% for students and 98% for evaluators. Conclusion: the Clinical Competence Questionnaire was translated and adapted to Brazilian students, and the psychometric properties of the Portuguese version of the questionnaire presented satisfactory internal consistency regarding the studied sample.